Promoter and nonspecific DNA binding by the T7 RNA polymerase. - Smeekens, S P (1986)
T7 RNA polymerase plays an important role in both the transcription and replication of bacteriophage T7. In this study we have used a nitrocellulose filter binding assay to examine the binding properties of the T7 RNA polymerase with T7 promoters cloned into plasmid DNAs. Promoter-specific binding was shown to be relatively insensitive to variations in the ionic strength of the incubation solution but dependent on the helical structure of the DNA. On the other hand, nonpromoter interior-site binding was independent of the superhelicity of the DNA but extremely sensitive to changes in the ionic strength. These results suggest that nonspecific binding results from ionic interactions between positively charged residues of the polymerase and the polyanionic backbone of the DNA, whereas promoter-specific binding is dependent upon base-specific contacts within the promoter sequence. A comparison between the transcriptional activity and binding strengths of the RNA polymerase to specific promoters indicates little correlation between these two properties. This suggests that differential promoter binding does not represent a major mechanism for regulating transcription in bacteriophage T7. Instead, factors which influence the efficiency or rate of formation of the polymerase-promoter open complex are found to have the major role in determining transcriptional levels in this system.